PHOTOVOICE AS A TOOL TO IMPROVE PATIENT - PROVIDER COMMUNICAITON IN INFLAMMATORY BOWEL DISEASE CLNIIC: A PILOT OF FEASIBILITY STUDY. (21st January 2021) - Gorbenko, Ksenia; Riggs, Alexa; Phlegar, Sydney; Koeppel, Brooke; Dubinsky, Marla; Ungaro, Ryan; Keefer, Laurie
Abstract: Introduction: The emotional health of patients with IBD has been difficult to elucidate in routine IBD care, but is critical to medication adoption, adherence and self-management. Patients often are unsure how to communicate their preferences and concerns to their providers in ways that could directly inform shared decision making. Photovoice is an established research methodology used to give vulnerable patients a voice through alternative communication strategies, but has not been previously used in IBD. Aim: Our goal was to determine the acceptability and feasibility of developing a communication tool using photovoice in an IBD clinic. The ultimate goal is to adapt Photovoice to facilitate doctor – patient communication around treatment and wellness goals in the clinic setting. Methods: We recruited patients at a single tertiary care IBD center in 2019 to participate in a pilot Photovoice study. Patients received a digital camera, training on basic usage and 10 disease specific prompts focused on goals/strategies they used to manage IBD. For example, "What is the most important thing for your doctor to know about you?" Patients then participated in in-depth interviews where they shared the photos they took and described rationale for their photo choice. The interviews lasted approximately one hour and were audio recorded and professionally transcribed. Three analysts coded transcripts for themes using qualitative analysis software QSR NVivo 11. Subsequently, five physicians were recruited and also participated in in-depth interviews to gauge provider feasibility of incorporating Photovoice into clinical practice. Results: Fifteen patients were enrolled, median age 28 IQR (24–40), 66% women, 86% white. Three patients (20%) identified as Hispanic and six (40%) identified as Ashkenazi Jewish. Fourteen transcripts were available for analysis (9 patient and 5 providers). A total of 87 photos were taken and reviewed with patients, with a subset of 15 photos reviewed with physicians. The general themes from patients were physical and psychological aspects of disease, logistical/practical aspects, and future with IBD. Physician response was overwhelmingly supportive of incorporating Photovoice into clinical practice and suggested several ways to incorporate: 1. As discrete parts of visits to foster goal-setting and identify patient priorities. 2. Displayed in the hallways of the clinic to foster community among patients. 3. As part of electronic medical records or as prompts in the waiting room to generate referrals to other resources like psychotherapy, social work and diet consults. Conclusions: Photovoice is a feasible methodology for patients with IBD and acceptable to providers to use in a clinical setting. Photovoice may help providers identify patient concerns and tailor their communication and enhance approaches to shared decision making.